Using Mind Mapping to Teach Speaking Skill to the Tenth Grade Students of MAN Palopo - Riska; Andi Tenrisanna Syam (Faculty of Education and Teacher Training of IAIN Palopo, 2021)
The purpose of this research is to find out whether the students who are taught by using mind mapping have better achievement than the students who were taught by using a non-mapping strategy. This research used a quasi-experimental method. The population of this research consisted of tenth-grade students of MAN Palopo. The writer used purposive sampling, where there were two classes as the sample. They were; class X MIA I and X MIA II. Each class consisted of 30 students. The writer gave pretest and posttest to the students—three aspects of speaking skill assessed, namely accuracy, fluency, and comprehensibility. The result of this research shows that the students who were taught by using mind mapping did not have better achievement than the students who were taught by using non-mind mapping. The data showed that t-obtained was higher than t-table (t-o > t-table). The findings of t-obtained were 0.216, whereas the level of significance of 0.05 (5%) was 2.002. It means that 2.002 ≥ 0.216. The orienting number of significance shows that 0.830 > 0.05. Therefore, the Null Hypothesis (H0) accepted, and the Alternative Hypothesis (H1) rejected. Some problems found by the writer namely, the students switch code to speak up because they did not know the English meaning of the words, the students still read the text to speak because they did not memorize the language pattern that had been given. So, they had difficulties in speaking without reading the text. They felt hungry, tired, and bored in the class, and some of the students had meetings’ organization after they were an exam.